PEMBERDAYAAN PAGUPON LITERASI SEBAGAI UPAYA MENUMBUHKAN MINAT BACA BAGI SISWA DI SD MUHAMMADIYAH BANTUL KOTA DI ERA REVOLUSI INDUSTRI 4.0 - Maya Kartika Sari; Suyanti Suyanti; Vivi Rulviana; Rodiyatun Rodiyatun (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This study aims to determine: 1). Implementation of paguponliteracy at Muhammadiyah Bantul City Elementary School; 2) To what extent Pagupon literacy can increase reading interest in students; 3). The role of schools in empowering literacy pagupons as an effort to increase student interest in reading at SD Muhammadiyah Bantul Kota. This study uses a qualitative phenomenological approach. Sources of data are teachers, principals, librarians, data collection techniques by observation and interviews. The data analysis technique used source triangulation and technical triangulation. The research results are as follows: 1). Muhammadiyah Bantul City Elementary School has empowered literacy through literacy pagupon effectively and optimally. It is proven that many students like to visit the pagupon which is in the front yard of the school library, the students are diligent in reading the books placed on the pagupon, the students are enthusiastic and interested in continuing to take books from the pagupon to be studied in turn; learning is not only done in the classroom but also in front of the pagupon (Pagupon literacy camp); 2) The existence of the pagupon can attract students to read the books provided in the paguponliteracy. 3) The role of teachers, school principals and librarians is very optimal in providing exemplary, improving facilitiesÂ and books in the pagupon, the teacher invites students to always analyze books read together, and motivates students to always visit pagupons to increase knowledge.Â